The inclusive language debate a plea for realism - Carson, Don A. (Grand Rapids, MI Baker, 1998)
Includes bibliographical references and indexes.
Keywords: Bible -- translating; Nonsexist language -- religious aspects -- Christianity; Bible. English -- versions